Student Response to Rulisca Learning Media Implementation Toward Science Learning in IV Class Elementary School - Ari Suryawan; Irena Dara Melfia; Desti Shinta Kurniawati; Shinta Futichatul’ Aini; Rosidatul Muawana (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to determine the response of students to Rulisca learning media with the Problem Based Learning learning model at Muntilan Elementary School. This study uses a descriptive approach to analysis of student responses in the study of the implementation of learning media. The subjects of the study were grade IV students totaling 18 students through purposive sampling techniques. The results of the study were obtained from the questionnaire sheet of student responses in learning related to energy change material. Based on the results of a study consisting of 10 statements, it shows that Rulisca's learning media received a Considerably Interested. This is influenced because the media used uses the application of renewable technology to the concept of energy change. Rulisca makes students have a high curiosity to build their thinking constructions. Learning media used in energy change by involving solar cell technology and assembling supporting devices make students understand and are excited to understand energy changes contextually, besides that the use of Problem Based Learning learning models also makes students to think critically and logically in understanding problems. Stages in the learning model also make students feel more enthusiastic in the learning process.